The integration of Sustainable Development Goals (SDG) in the Pedagogical Projects of Accounting Courses in Brazil - Aguiar, José Hilton Santos; Gomes, Sonia Maria da Silva; Monteiro, Sónia Maria da Silva; Freire, Fátima de Souza (Revista de Administração da UFSM, 2024)
Purpose: The study aims to analyze how Brazilian Higher Education Institutions (HEIs) with the highest scores in the last National Student Performance Exam (NESP 2018) are integrating the Sustainable Development Goals (SDGs) into the Pedagogical Projects of their Accounting Courses. Design/methodology/approach: Content analysis was performed on 11 Pedagogical Projects of Courses (PPCs), examining 118 categories related to the 17 SDGs and their goals. Findings: SDG 4 (Quality Education) and SDG 9 (Industry, Innovation, and Infrastructure) were found in all PPCs. SDG 2 (Zero Hunger and Sustainable Agriculture), SDG 10 (Reduced Inequalities), and SDG 8 (Decent Work and Economic Growth) appeared in 81.8%, 72.7%, and 54.5% of the PPCs, respectively. On the other hand, no results were found for SDG 14 (Life Below Water), SDG 15 (Life on Land), and SDG 17 (Partnerships for the Goals). For SDGs 4 and 9, we found associations with the corresponding targets 9.5, 9.b, 4.3, 4.4, 4.5, and 4.7. Originality/value: This study represents the first Brazilian effort to understand the pedagogical approaches to the SDGs in Accounting courses within Higher Education Institutions in Brazil. It stands out for using innovative methods, still rarely explored in accounting research, combining qualitative approaches and content analysis with the support of NVIVO software.